Strategi Koordinasi Antar Unit Kerja dalam Mencegah Keterlambatan Pengajuan Klaim BPJS di Rumah Sakit Jannah Kota Serang - Mayang Wulandari; Rian Andriani; Kahar Mulyani (VISA: Journal of Vision and Ideas, 2026)
Delays in submitting BPJS claims are a crucial challenge in the hospital financing system, having a direct impact on cash flow and service quality. At Jannah Hospital in Serang City, this problem is chronic, with pending claims reaching hundreds of cases and receivables value of hundreds of millions of rupiah. This study aims to examine the coordination strategy between work units in preventing delays in submitting BPJS claims, using Henry Mintzberg's coordination theory approach which includes five mechanisms: mutual adjustment, direct supervision, work process standardization, output standardization, and skill standardization. The methodology used is a qualitative approach with a case study design. Data collection techniques include in-depth interviews, participatory observations, and document studies. The research informants totaled 21 people consisting of structural officials, medical staff, administration, casemix, and other related units. The data were analyzed using thematic analysis methods to identify coordination patterns and key barriers. The results of the study showed weak coordination systems across units as the main cause of delays. It was found that strengthening direct supervision and standardization of work processes is a key strategy. This study recommends the establishment of cross-unit SOPs, improved staff skills training, and integrated reporting systems as solutions to speed up and streamline the claims process.